Synergistic effects of selenium nanoparticles and LED light on enhancement of secondary metabolites in sandalwood (Santalum album) plants through in-vitro callus culturing technique - Mazhar, Muhammad Waqas; Ishtiaq, Muhammad; Maqbool, Mehwish; Jafri, Faisal Iqbal; Siddiqui, Manzer H.; Alamri, Saud; Akhtar, Mohd Sayeed (PeerJ, 2024)
The yield and concentration of secondary metabolites (SMs) in plants can vary due to numerous challenges such as dynamic environmental conditions, moisture, soil quality, soil organic matter and plant genetics. To obtain a good yield of SMs novel elicitation approaches, such as the use of biotic and abiotic stressors, genetic modifications, and optimized growth conditions, have been practiced, particularly the use of selenium nanoparticles (SeNPs) and light emitting diode (LED) interaction through employing tissue culture technique. In the present study, in vitro callus cultures of sandalwood (Santalum album L.) were subjected to elicitation with different concentrations of SeNPs with doses of 30 µg/L, 60 µg/L, and 90 µg/L in combination with green (∼550 nm), red (∼660 nm) and blue (∼460 nm) LED lights. Interaction of these treatments produced 16 treatments replicated three times in 48 test tubes. The results were analysed using two-way ANOVA and Tukey’s HSD test. The study revealed that synergistic interaction between SeNPs and LED light wavelengths significantly enhanced callus growth and secondary metabolite (SM) production eliciting callus cultures with blue LED light and a dose of 90 µg/L SeNPs resulted in an increase in callus growth including fresh weight, dry weight, and the number of shoot branches per callus. This combined treatment positively influenced the functions of major bioactive antioxidants such as superoxide dismutase (SOD), peroxidase (POD), catalase (CAT) and phenylalanine ammonia-lyase (PAL). Furthermore, the concentrations of essential secondary metabolites, including total phenolic, total saponins, casein/BSA/PVPP-bound tannins, flavan-3-ols, and tocopherols experienced substantial elevation under the synergistic influence of SeNPs and LED light conditions. The sandalwood plants produced through the callus culturing technique using optimized SeNPs and LED lights show an enhanced yield of secondary metabolites, which will be very useful and potential for pharmaceutical, cosmetic and various other industries to discover and develop novel products.
Keywords: Elicitation; Tissue culture; Bioactive antioxidants; Seleniumnanoparticle; Sandalwood